2020
DOI: 10.32598/jmr.15.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effect of High Power Laser on Quadriceps Muscle Performance in Male Football Players: A Single-Group, Pretest-Posttest Trial

Abstract: Introduction: The use of High Power Laser (HPL) has recently been emphasized in physiotherapy. Previous studies suggest that the prophylactic use of laser has ergogenic effects on athletic performance by increasing the contractile function of skeletal muscles. Recently, muscle function improvement is a new research idea in the field of laser therapy. Based on our knowledge, there are only two studies on the effects of HPL on muscle performance although with contradictory results. The purpose of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Physical therapy, cold therapy, orthotics, bracing, and taping are some of the non-pharmacological treatment options for treating this syndrome 9 . HPL shows immediate results and researchers have reported that a single session or use of HPL significantly improves quadriceps muscle function 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Physical therapy, cold therapy, orthotics, bracing, and taping are some of the non-pharmacological treatment options for treating this syndrome 9 . HPL shows immediate results and researchers have reported that a single session or use of HPL significantly improves quadriceps muscle function 10 .…”
Section: Introductionmentioning
confidence: 99%